Co-solvent slurry system for solution processing of sulfide solid state batteries

By using a synergistic co-solvent composition of low polarity solvent and ether-based solvent, the problem of reaction between solvent and battery components in the prior art is solved, the stability and life of the battery pack are improved, and the working temperature is expanded scope.

CN119495822APending Publication Date: 2025-02-21GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311048632.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the prior art, the solvent N-methylpyrrolidone (NMP) used to manufacture sulfide solid battery packs is prone to react with other components in the battery packs, resulting in a degradation of battery performance.

Method used

A synergistic cosolvent composition using a low polar solvent and an ether-based solvent is used to mix with the active material, the conductive material and the solid electrolyte to form an electrode to form a slurry, and avoid reaction with the electrolyte.

Benefits of technology

By using a synergistic cosolvent composition, the reaction between the electrode and the electrolyte is successfully avoided, the stability and life of the battery pack is improved, and it is allowed to operate effectively over a wide operating temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495822A_ABST
    Figure CN119495822A_ABST
Patent Text Reader

Abstract

A method of making an electrode forming slurry includes mixing an active material, a conductive material, and optionally a solid electrolyte with a low polarity solvent. The low polarity solvent has a dipole moment less than 4 and a boiling point greater than 100 DEG C to form a first slurry, wherein the active material is an anode active material or a cathode active material. A polymeric binder and an ether-based solvent are mixed to form a second slurry. The first slurry is mixed with the second slurry to form an electrode forming slurry.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] introduction

[0002] The present disclosure relates to a co-solvent slurry system for sulfide solid-state batteries. More specifically, it relates to an ether-based co-solvent slurry system for solution processing of sulfide solid-state batteries.

[0003] All-solid-state batteries (ASSBs) employing sulfide electrolytes have the potential to outperform state-of-the-art lithium-ion batteries (LIBs) in terms of abuse tolerance and operating temperature range. Prototype ASSBs were fabricated using a wet coating method that employs solvents and binders to fabricate sheet-type electrodes. However, the most commonly used solvent in batteries is N-methylpyrrolidone (NMP), which unfortunately reacts with other ingredients, especially those used in sulfide solid-state batteries.

[0004] It would therefore be desirable to provide a solvent that can be used to prepare an electrolyte that does not react with the various ingredients used in a battery. SUMMARY OF THE INVENTION

[0006] This application involves the following:

[0007] [1] A method for manufacturing an electrode forming slurry, comprising:

[0008] Mixing an active material, a conductive material, and an optional solid electrolyte together with a low polarity solvent; wherein the low polarity solvent has a dipole moment of less than 4 and a boiling point greater than 100° C. to form a first slurry; wherein the active material is an anode active material or a cathode active material;

[0009] mixing a polymer binder and an ether-based solvent together to form a second slurry; and

[0010] The first slurry is mixed with the second slurry to form an electrode-forming slurry.

[0011] [2] The method as described in [1] above, further comprising placing the electrode forming slurry on a current collector and subjecting the current collector to an elevated temperature.

[0012] [3] The method as described in [2] above further includes drying the electrode forming slurry to form an electrode.

[0013] [4] The method as described in [1] above, wherein the low polarity solvent has a structure represented by the following formula:

[0014] C n H 2n+2 (1);

[0015] or

[0016] C n H2n (2);

[0017] wherein C is carbon, H is hydrogen, and n is an integer greater than 5, and wherein the structure of formula (1) or formula (2) is substituted or unsubstituted.

[0018] [5]. The method as described in [1] above, wherein the low polarity solvent is pentane, cyclopentane, hexane, cyclohexane, heptane and isomers thereof, toluene, ethylbenzene, p-xylene, m-xylene, o-xylene, anisole or a combination thereof.

[0019] [6]. The method as described in [1] above, wherein the low-polarity solvent is anisole.

[0020] [7] The method as described in [1] above, wherein the ether-based solvent comprises an ether having a structure defined by formula (3):

[0021] C 2n H 2n+2 O (3),

[0022] wherein C is carbon, H is hydrogen, O is oxygen, and wherein n is an integer greater than 1; and wherein the structure of formula (3) is substituted or unsubstituted.

[0023] [8]. The method as described in [1] above, wherein the ether-based solvent is dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, dimethoxymethane, tetraethylene glycol, methyl tert-butyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, tetrahydrofuran (THF), dioxane, diisopropyl ether, 2-butoxyethanol, cyclopentyl methyl ether, 2-methyltetrahydrofuran or a combination thereof.

[0024] [9]. The method as described in [1] above, wherein the ether-based solvent is dimethyl ether.

[0025]

[10] The method as described in [1] above, wherein the solid electrolyte is a pseudo-binary sulfide, a pseudo-ternary sulfide, a pseudo-quaternary sulfide or a combination thereof.

[0026]

[11] . The method as described in [1] above, wherein the solid electrolyte is Li6PS5Cl.

[0027]

[12] A method for manufacturing a solid electrolyte for a solid-state battery, comprising:

[0028] A low polarity solvent and an ether-based solvent are mixed with a solid electrolyte and a polymer binder; wherein the low polarity solvent has a dipole moment less than 4 and a boiling point greater than 100° C.; wherein the solid electrolyte is a pseudo-binary sulfide, a pseudo-ternary sulfide, a pseudo-quaternary sulfide, or a combination thereof.

[0029]

[13] . The method as described in

[12] above, wherein the polymer binder is poly(vinylidene fluoride-co-chlorotrifluoroethylene), poly(vinylidene fluoride-trifluoroethylene), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer, poly(vinylidene fluoride-hexafluoropropylene) or a combination thereof.

[0030]

[14] A battery pack comprising:

[0031] Anode current collector;

[0032] An anode active layer disposed on the anode current collector; wherein the anode active layer comprises an anode active material; a polymer binder and a conductive additive;

[0033] cathode current collector;

[0034] A cathode active layer disposed on a cathode current collector; wherein the cathode active layer comprises a cathode active material; a polymer binder, a solid electrolyte, and a conductive additive; and

[0035] A solid electrolyte; wherein the solid electrolyte contacts an anode active layer and a cathode active layer; and wherein the solid electrolyte comprises a blend of a polymer binder and a pseudo binary sulfide, a pseudo ternary sulfide, a pseudo quaternary sulfide, or a combination thereof.

[0036]

[15] The battery pack as described in

[14] above, wherein the anode active material is hard carbon, silicon, silicon mixed with graphite, carbon-coated silicon particles, Li4Ti5O 12 ; transition metal, metal sulfide, lithium metal or lithium metal alloy or a combination thereof.

[0037]

[16] . A battery pack as described in

[14] above, wherein the cathode active material is lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate oxide, lithium nickel cobalt aluminum oxide, spinel or a combination thereof.

[0038]

[17] . The battery pack as described in

[16] above, wherein the lithium nickel manganese cobalt oxide is LiNi x Mn y Co (1-x-y) O2; the lithium nickel cobalt aluminum oxide is LiNi x Mn y Al (1-x-y) O2, the lithium nickel manganese oxide is LiNi x Mn (1-x) O2, wherein in each case x is from 0.7 to 0.85 and y is less than 0.15.

[0039]

[18] . A battery pack as described in

[14] above, wherein the solid electrolyte comprises a Li2S-P2S5 system, a Li2S-SnS2 system, a Li2S-SiS2 system, a Li2S-GeS2 system, a Li2S-B2S3 system, a Li2S-Ga2S3 system, a Li2S-P2S3 system, a Li2S-Al2S3 system, a Li2O-Li2S-P2S5 system, a Li2S-P2S5-P2O5 system, a Li2S-P2S5-GeS2 system, a Li2S-P2S5-LiX system, wherein X=F, Cl, Br or I; a Li2S-As2S5-SnS2 system, a Li2S-P2S5-Al2S3 system, a Li2S-LiX-SiS2, wherein X=F, Cl, Br or I.

[0040]

[19] A battery pack as described in

[14] above, wherein the solid electrolyte is Li6PS5Cl.

[0041]

[20] . The battery pack as described in

[14] above, wherein the polymer binder is poly(vinylidene fluoride-hexafluoropropylene).

[0042] In an exemplary embodiment, a method for making an electrode forming slurry includes mixing an active material, a conductive material, and an optional solid electrolyte with a low polarity solvent. The low polarity solvent has a dipole moment of less than 4 and a boiling point greater than 100° C. to form a first slurry, wherein the active material is an anode active material or a cathode active material. A polymer binder and an ether-based solvent are mixed to form a second slurry. The first slurry is mixed with the second slurry to form an electrode forming slurry.

[0043] In another exemplary embodiment, the electrode-forming slurry is disposed on a current collector and the current collector is subjected to an elevated temperature.

[0044] In yet another exemplary embodiment, the electrode forming slurry present on the current collector is dried to form an electrode.

[0045] In yet another exemplary embodiment, the low polarity solvent has the formula C n H 2n+2 (1); or C n H 2n (2) wherein C is carbon, H is hydrogen, and n is an integer greater than 5, and wherein the structure of formula (1) or formula (2) is substituted or unsubstituted.

[0046] In yet another exemplary embodiment, the low polarity solvent is pentane, cyclopentane, hexane, cyclohexane, heptane and isomers thereof, toluene, ethylbenzene, p-xylene, m-xylene, o-xylene, anisole, or a combination thereof.

[0047] In yet another exemplary embodiment, the low polarity solvent is anisole.

[0048] In yet another exemplary embodiment, the ether-based solvent comprises an ether having a structure defined by formula (3):

[0049] C 2n H 2n+2 O (3),

[0050] wherein C is carbon, H is hydrogen, O is oxygen, and wherein n is an integer greater than 1; and wherein the structure of formula (3) is substituted or unsubstituted.

[0051] In yet another exemplary embodiment, the ether-based solvent is dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, dimethoxymethane, tetraethylene glycol, methyl tert-butyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, tetrahydrofuran (THF), dioxane, diisopropyl ether, 2-butoxyethanol, cyclopentyl methyl ether, 2-methyltetrahydrofuran, or a combination thereof.

[0052] In yet another exemplary embodiment, the ether-based solvent is dimethyl ether.

[0053] In yet another exemplary embodiment, the solid-state electrolyte is a pseudo-binary sulfide, a pseudo-ternary sulfide, a pseudo-quaternary sulfide, or a combination thereof.

[0054] In yet another exemplary embodiment, the solid state electrolyte is Li6PS5Cl.

[0055] In an exemplary embodiment, a method for making a solid electrolyte for a solid-state battery includes mixing a low polarity solvent and an ether-based solvent with a solid electrolyte and a polymer binder. The low polarity solvent has a dipole moment of less than 4 and a boiling point greater than 100° C. The solid electrolyte is a pseudobinary sulfide, a pseudoternary sulfide, a pseudoquarternary sulfide, or a combination thereof.

[0056] In an exemplary embodiment, the polymer binder is poly(vinylidene fluoride-co-chlorotrifluoroethylene), poly(vinylidene fluoride-trifluoroethylene), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer, poly(vinylidene fluoride-hexafluoropropylene), or a combination thereof.

[0057] In an exemplary embodiment, the battery pack includes an anode current collector and an anode active layer disposed on the anode current collector. The anode active layer comprises an anode active material, a polymer binder, and a conductive additive. The battery pack also includes a cathode current collector and a cathode active layer disposed on the cathode current collector. The cathode active layer comprises a cathode active material, a polymer binder, a solid electrolyte, and a conductive additive. The battery pack also includes a solid electrolyte, wherein the solid electrolyte contacts the anode active layer and the cathode active layer. The solid electrolyte comprises a blend of a polymer binder and a pseudo binary sulfide, a pseudo ternary sulfide, a pseudo quaternary sulfide, or a combination thereof.

[0058] In an exemplary embodiment, the anode active material is hard carbon, silicon, silicon mixed with graphite, carbon-coated silicon particles, Li4Ti5O 12 ; transition metal, metal sulfide, lithium metal or lithium metal alloy or a combination thereof.

[0059] In yet another exemplary embodiment, the cathode active material is lithium cobalt oxide, lithium nickel manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate oxide, lithium nickel cobalt aluminum oxide, spinel, or a combination thereof.

[0060] In yet another exemplary embodiment, the lithium nickel manganese cobalt oxide is LiNi x Mn y Co (1-x-y) O2; the lithium nickel cobalt aluminum oxide is LiNi x Mn y Al (1-x-y) O2, the lithium nickel manganese oxide is LiNi x Mn (1-x) O2, wherein in each case x is from 0.7 to 0.85 and y is less than 0.15.

[0061] In another exemplary embodiment, the solid-state electrolyte includes a Li2S-P2S5 system, a Li2S-SnS2 system, a Li2S-SiS2 system, a Li2S-GeS2 system, a Li2S-B2S3 system, a Li2S-Ga2S3 system, a Li2S-P2S3 system, a Li2S-Al2S3 system, a Li2O-Li2S-P2S5 system, a Li2S-P2S5-P2O5 system, a Li2S-P2S5-GeS2 system, a Li2S-P2S5-LiX system, wherein X=F, Cl, Br or I; a Li2S-As2S5-SnS2 system, a Li2S-P2S5-Al2S3 system, a Li2S-LiX-SiS2, wherein X=F, Cl, Br or I.

[0062] In yet another exemplary embodiment, the solid state electrolyte is Li6PS5Cl.

[0063] In yet another embodiment, the polymer binder is poly(vinylidene fluoride-hexafluoropropylene).

[0064] The above features and advantages and other features and advantages of the present disclosure are apparent from the following detailed description when taken in conjunction with the accompanying drawings.

[0065] BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Additional features, advantages and details are set forth, by way of example only, in the following detailed description, which refers to the accompanying drawings, in which:

[0067] Figure 1 is an exemplary depiction of a solid-state battery pack disclosed herein;

[0068] Figure 2 is an exemplary depiction of a method of making a cathode active layer as described in Example 1; and

[0069] Figure 3A is a graph of voltage vs capacity for the first charge and discharge cycle measured on experimental and comparative battery packs at a constant current rate of 0.2C;

[0070] Figure 3B is a graph of the measured capacity vs. cycle time for the experimental and comparative battery packs. These measurements were performed at variable current rates of 0.2C, 0.5C, 1C, 2C, 3C, and 5C; and

[0071] Figure 3C is a graph measuring the capacity of the experimental and comparative cells versus cycle time when cycled at a current rate of 0.5C at room temperature. DETAILED DESCRIPTION OF THE INVENTION

[0073] The following description is merely exemplary in nature and is not intended to limit the present disclosure, its application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate the same or corresponding parts and features.

[0074] According to an exemplary embodiment, a synergistic co-solvent composition comprising a first solvent having low polarity (hereinafter referred to as a "low polarity" solvent) and a second solvent comprising an ether bond is used to solvate a polymer binder for an electrode of a sulfide all-solid-state battery (hereinafter referred to as a sulfide solid-state battery). The all-solid-state battery exhibits properties (such as their operating temperature range) that allow them to compete commercially with conventional lithium-ion batteries. The sulfide solid-state battery contains a sulfide electrolyte, and the use of a synergistic co-solvent composition to solvate the polymer binder prevents any reaction between the electrode and the electrolyte.

[0075] Also disclosed herein is a method for manufacturing an electrode, comprising mixing a synergistic co-solvent with a polymer binder, a conductive additive, an active agent, and an optional solid electrolyte to form an electrode active material composition (in the form of a slurry), which is then disposed on a current collector to form an active layer. The current collector on which the slurry is disposed is further processed to form an electrode. The electrode can be an anode or a cathode, depending on the composition of the slurry disposed thereon. In short, the electrode active material composition used to make the anode is different from the electrode active material composition used to make the cathode. These compositional differences will be discussed in detail later.

[0076] Also disclosed herein is a method for making an electrolyte composition, which includes mixing a synergistic co-solvent with a polymer binder and a solid electrolyte. The corresponding electrodes (i.e., cathode and anode) and the electrolyte composition can then be combined in a housing to form a solid-state battery. Each component used to make the corresponding electrode and the method for making the electrode and the electrolyte are described in detail below.

[0077] Figure 1 A cross section of an exemplary solid-state battery 100 is depicted, comprising an anode current collector 102, an anode active layer 104 disposed on the anode current collector 102, a solid electrolyte 106, a separator 108, and a cathode active layer 110 disposed on a cathode current collector 112. The various components of the solid-state battery 100 are contained in a housing 200, which includes terminals 202 and 204 that are typically electrically connected to a load (not shown). The anode current collector 102 and the cathode current collector 112 typically comprise a metal. In one embodiment, the anode current collector 102 comprises stainless steel, copper, nickel, iron, titanium, or a combination thereof, and the cathode current collector 112 comprises stainless steel, aluminum, nickel, iron, titanium, or a combination thereof.

[0078] The anode active layer 104 and the cathode active layer 110 are generally manufactured by preparing an anode active material slurry and a cathode active material slurry and disposing the respective slurries on the anode current collector 102 and the cathode current collector 112. When the slurry is dried (i.e., all solvents used in the slurry are removed), the anode of the solid-state battery 100 includes the anode current collector 102 and the anode active layer 104 disposed thereon, and the cathode includes the cathode current collector 112 and the cathode active layer 110 disposed thereon.

[0079] The solid-state electrolyte 106 surrounds the anode and cathode. The separator 108 is optional - it typically comprises an electrically insulating material and may not be present in the solid-state battery 100 if desired.

[0080] The slurry for preparing the anode active layer 104 is called an electrode forming slurry and comprises a synergistic co-solvent composition, a conductive additive, an anode active material and a polymer binder. Since these ingredients are commonly used to form an anode active layer, the combination is sometimes also referred to as an anode active material slurry. The synergistic co-solvent composition, the conductive additive, the anode active material and the polymer binder are mixed to form a slurry, which is then placed on the anode current collector 102 and allowed to dry. The dried slurry forms the anode active layer 104, and it contacts the anode current collector 102 to form an anode.

[0081] The slurry used to prepare the cathode active layer 110 is also referred to as an electrode forming slurry (because it contains most of the same ingredients as the slurry used to form the anode active layer), and includes a synergistic co-solvent composition, a conductive additive, a cathode active material, and a polymer binder. Since these ingredients are generally used to form a cathode active layer, the combination is sometimes also referred to as a cathode active material slurry. The synergistic co-solvent composition, the conductive additive, the cathode active material, and the polymer binder are mixed to form a slurry, which is then placed on the cathode current collector 112 and allowed to dry. The dried slurry forms the cathode active layer 110, and it contacts the cathode current collector 112 to form a cathode.

[0082] In one embodiment, the synergistic co-solvent composition comprises a first solvent having low polarity (hereinafter referred to as a "low polarity" solvent) and a second solvent comprising an ether bond. The synergistic co-solvent composition thus comprises a plurality of solvents, one of which solubilizes the polymer binder, while another solvent can be used to disperse the conductive additive and the active material, thereby obtaining a uniform dispersion of these ingredients in the polymer binder. The synergistic co-solvent composition does not react with the solid electrolyte, which maintains the life of the battery.

[0083] The first solvent (low polarity solvent) comprises a substituted or unsubstituted straight chain, cyclic or aromatic hydrocarbon-based solvent having a dipole moment of less than 4.0, preferably less than 3.5, preferably less than 3.0, preferably less than 2.0, and more preferably less than 1.75. The low polarity solvent preferably has a boiling point greater than 100°C. By using a low polarity solvent, the sulfide solid electrolyte can not only maintain its chemical structure and ionic conductivity, but also can be uniformly mixed with active materials and carbon during the mixing process to form a slurry, which is disposed on a current collector to form a corresponding electrode. The slurry is disposed on a current collector to facilitate the formation of an electrode, and is therefore sometimes referred to as an electrode forming slurry. The terms "slurry" and "electrode forming slurry" are therefore used interchangeably.

[0084] The low polarity solvent is preferably in liquid form at room temperature (23° C.) and pressure, and has a structure represented by the following formula (which may be substituted or unsubstituted):

[0085] Cn H 2n+2 (1); or

[0086] C n H 2n (2);

[0087] wherein C is carbon, H is hydrogen, and n is an integer greater than 5, preferably greater than 6. The term "substituted" means that at least one hydrogen atom on the group is replaced by another atom or group, provided that the normal valence of the designated atom is not exceeded. Exemplary groups that may be present in a "substituted" position include, but are not limited to, nitro (-NO2), cyano (-CN), hydroxyl (-OH), oxo (=O), amino (-NH2), mono- or di-(C 1-6 ) alkylamino, alkanoyl (such as C 2-6 Alkanoyl, such as acyl), formyl (-C(=O)H), carboxylic acid or its alkali metal or ammonium salt; ester (including acrylate, methacrylate and lactone) such as C 2-6 Alkyl esters (-C(=O)O-alkyl or -OC(=O)-alkyl) and C 7-13 Aryl ester (-C(=O)O-aryl or -OC(=O)-aryl); amide (-C(=O)NR2, where R is hydrogen or C 1-6 alkyl), carboxamido (-CH2C(=O)NR2, wherein R is hydrogen or C 1-6 alkyl), halogen, mercapto (-SH), C 1-6 Alkylthio (-S-alkyl), thiocyano (-SCN), C 1-6 Alkyl, C 2-6 Alkenyl, C 2-6 Alkynyl, C 1-6 Haloalkyl, C 1-9 Alkoxy, C 1-6 Haloalkoxy, C 3-12 Cycloalkyl, C 5-18 Cycloalkenyl, C 6-12 Aryl (e.g., phenyl, biphenyl, naphthyl, etc., each ring is a substituted or unsubstituted aromatic ring), C having 1 to 3 independent or condensed rings and 6 to 18 ring carbon atoms 7-19 Arylalkyl, arylalkoxy having 1 to 3 separate or fused rings and 6 to 18 ring carbon atoms, C 7-12 Alkyl aryl, C 4-12 Heterocycloalkyl, C 3-12 Heteroaryl, C 1-6 Alkylsulfonyl (-S(=O)2-alkyl), C 6-12Arylsulfonyl (-S(=O)2-aryl) or tosyl (CH3C6H4SO2-). When a group is substituted, the number of carbon atoms shown is the total number of carbon atoms in the group, not including the number of carbon atoms of any substituents. For example, the group -CH2CH2CN is a C2 alkyl substituted with a cyano group. The substitutions listed above can occur as long as the dipole moment of the resulting molecule is less than 2.0.

[0088] Examples of low polarity solvents include pentane, cyclopentane, hexane, cyclohexane, heptane and isomers thereof, toluene, ethylbenzene, p-xylene, m-xylene, o-xylene, anisole or a combination thereof. Anisole is preferred.

[0089] The concentration of the first solvent ("low polarity" solvent) in the synergistic co-solvent composition is 10 to 60 weight percent (wt%), preferably 20 to 50 wt%, based on the total weight of the synergistic co-solvent composition.

[0090] The second solvent is an ether-based solvent that effectively solubilizes the adhesive used in the electrode. In one embodiment, the ether-based solvent includes one or more ether (-O-) bonds. The ether-based solvent effectively solubilizes the adhesive comprising poly (vinylidene fluoride). The adhesive can be a homopolymer, copolymer or polymer blend containing poly (vinylidene fluoride). In an exemplary embodiment, the ether-based solvent effectively solubilizes the adhesive comprising poly (vinylidene fluoride-to-hexafluoropropylene) (PVDF-HFP) copolymer. Based on the total weight of the adhesive and the ether-based solvent, the total concentration of the adhesive in the ether-based solvent is 5 to 50 weight %, preferably 6 to 10 weight %.

[0091] The ether-based solvent comprises an ether having a structure defined by formula (3)

[0092] C 2n H 2n+2 O (3),

[0093] wherein C is carbon, H is hydrogen, O is oxygen, and wherein n is an integer greater than 1 (n>1).

[0094] The ether-based solvent may comprise a linear ether, a cyclic ether or a combination thereof. Although an asymmetric or symmetric ether-based solvent may be used, it is desirable to use a symmetric solvent. It is desirable to use an ether-based solvent having a boiling point of less than 100°C.

[0095] Examples of such solvents include dimethyl ether (DME), diethyl ether, dipropyl ether, dibutyl ether, dimethoxymethane, tetraethylene glycol, methyl tert-butyl ether, tetraethylene glycol dimethyl ether (TEGDME), diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, tetrahydrofuran (THF), dioxane, diisopropyl ether, 2-butoxyethanol, cyclopentyl methyl ether, 2-methyltetrahydrofuran or a combination thereof. Dimethyl ether is a preferred solvent.

[0096] The concentration of the second solvent ("ether-based" solvent) in the synergistic co-solvent composition is 40 to 90 wt%, preferably 50 to 80 wt%, based on the total weight of the synergistic co-solvent composition.

[0097] The synergistic co-solvent composition is used in an electrode-forming slurry (slurry that can be used to form an electrode) in an amount of 20 to 80 wt %, preferably 30 to 70 wt %, based on the total weight of the slurry.

[0098] As described above, the slurry used to form the electrode contains a conductive additive, a polymer binder, an active material (which may be an anode active material or a cathode active material, depending on the particular electrode (anode or cathode) in which it is used). The slurry may also contain a lithium-containing sulfide (which may also be used as an electrolyte) and a polymer binder.

[0099] The conductive additive preferably comprises a conductive carbonaceous material. Examples of conductive carbonaceous materials include carbon nanotubes, carbon black, activated carbon, graphene, graphite, graphite oxide, carbon fibers, etc., or a combination thereof. It is desirable that the conductive composition forms a conductive network extending from the current collector surface to the electrolyte surface.

[0100] Carbon nanotubes include single-walled carbon nanotubes (SWNT), double-walled carbon nanotubes (DWNT), multi-walled carbon nanotubes (MWNT) or combinations thereof and have a diameter of 2 to 100 nanometers, preferably 10 to 50 nanometers. They have a length of 20 to 10,000 nanometers, preferably 200 to 5000 nanometers. An aspect ratio greater than 10, preferably greater than 50 and more preferably greater than 100 is desirable.

[0101] Carbon black with a high surface area is preferred for electrodes. Carbon black (subclasses are acetylene black, channel black, furnace black, lamp black, and thermal black) is a material produced by the incomplete combustion of coal and coal tar, vegetable matter, or petroleum products (including fuel oil, fluid catalytic cracking tar, and ethylene cracked in limited supply of air). Carbon black is a form of quasi-crystalline carbon with a high surface area to volume ratio, although less than that of activated carbon. The surface area is 50 to 1000 m 2 / gm of carbon black may be used in the slurry used to form the electrode.

[0102] Activated carbon, also known as activated charcoal, is a carbon with a surface area of ​​more than 3,000 m 2 / gm of carbon form. It can be used in combination with other conductive carbonaceous elements listed herein. An example of carbon black or activated carbon that can be used in the electrode forming slurry is KELTJEN TM Black or Super P.

[0103] Graphene is an allotrope of carbon consisting of a single layer of atoms arranged in a hexagonal lattice nanostructure. The graphene added to the slurry can be in the form of individual graphene sheets or in the form of multiple loosely connected graphene sheets. Each atom in the graphene sheet is connected to its three nearest neighbors by σ bonds and delocalized π bonds, which contribute to a valence band that extends across the entire sheet. This is the same type of bonding seen in carbon nanotubes and polycyclic aromatic hydrocarbons, as well as in fullerenes and glassy carbon. The valence band is in contact with the conduction band, making graphene a semimetal with unusual electronic properties that are best described by theories for massless relativistic particles.

[0104] Graphite particles can also be used in conductive compositions. Graphite is a natural manifestation of pure carbon with a hexagonal crystal structure, which is arranged in several parallel layers, called graphene layers. In short, a graphite particle contains multiple graphene sheets arranged parallel to each other. This anisotropic structure gives graphite special properties, such as conductivity along the individual layers or specific strength. It is extremely heat-resistant, with a sublimation point of over 3,800°C, highly thermally conductive and chemically inert.

[0105] Graphite oxide (GO), sometimes called graphene oxide, graphite oxide or graphitic acid, is a compound of carbon, oxygen and hydrogen in variable ratios, obtained by treating graphite with strong oxidants and acids to resolve additional metals. The largest oxidized bulk product is a yellow solid with a C:O ratio of 2.1:1 to 2.9:1, which retains the layer structure of graphite, but has much larger and irregular spacing. The bulk material disperses spontaneously in an alkaline solution, or can be dispersed by ultrasonic treatment in a polar solvent to produce a monomolecular sheet, analogous to graphene, which is called graphene oxide, i.e., graphite in a monolayer form. Graphene oxide sheets exist in the form of strong paper-like materials, films, thin films and composite materials, and can be used in electrode forming slurries for preparing the electrode.

[0106] Carbon fibers have a diameter of 5 to 10 microns and are primarily composed of carbon atoms. They may have a length greater than 1000 microns, preferably greater than 10,000 microns. The carbon fibers are prepared by drawing pitch or polyacrylonitrile polymer fibers under high pressure and at a temperature exceeding 1500° C., preferably at a temperature above 2200° C. Carbon fibers are different from carbon nanotubes and do not have concentrically arranged cylindrical graphene sheets. Carbon fibers typically contain high aspect ratio graphene sheets arranged in parallel to each other.

[0107] The aforementioned carbon nanotubes, carbon black, activated carbon, graphene sheets, graphite particles, graphite oxide particles or combinations thereof may be used alone or in any combination to form a conductive network. In an exemplary embodiment, carbon nanotubes are generally used in the largest amount when compared to other carbonaceous components.

[0108] The active layer may contain the conductive additive in an amount of up to 5% by weight, preferably 1 to 4% by weight, based on the total weight of the active layer.

[0109] The electrode forming slurry also includes a polymer binder. The polymer binder binds the conductive additive and the active material so that they remain in contact with the current collector and do not disperse in the electrolyte during manufacturing or during use. The polymer binder preferably does not reduce the conductivity of the active layer disposed on the current collector. The active layer includes a conductive additive and a corresponding anode or cathode active material.

[0110] The polymer binder is preferably a fluorine-containing homopolymer or copolymer. In a preferred embodiment, the binder is a fluorine-containing copolymer. In one embodiment, the fluorine-containing copolymer is poly (vinylidene fluoride-co-chlorotrifluoroethylene) (abbreviated as P (VDF-CTFE)), poly (vinylidene fluoride-trifluoroethylene) (abbreviated as P (VDF-TeFE)), poly (vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) terpolymer (abbreviated as P (VDF-TrFE-CFE)), poly (vinylidene fluoride-hexafluoropropylene) (abbreviated as P (VDF-HFP) or PVDF-HFP) or at least one of its combination. In a preferred embodiment, the polymer binder used in the active layer is a poly (vinylidene fluoride-hexafluoropropylene) copolymer. The polymer binder has a weight average molecular weight of 5,000 to 1,000,000 g / mole, preferably 50,000 to 750,000 g / mole, and more preferably 75,000 to 500,000 g / mole as measured using gel permeation chromatography with polystyrene standards.

[0111] In one embodiment, the polyvinylidene content of any of the aforementioned binders is 80 to 95 weight percent based on the total weight of the polymer binder. The remaining polymer content of the copolymer is 5 to 20 weight percent based on the total weight of the polymer binder. For example, if the polymer binder is a poly(vinylidene fluoride-hexafluoropropylene) copolymer, the polyvinylidene content of the copolymer is 80 to 95 weight percent based on the total weight of the polymer binder, and the polyhexafluoropropylene content of the copolymer is 5 to 20 weight percent based on the total weight of the copolymer.

[0112] After removing the solvent, the total weight of the polymer binder in the active layer is less than 10 weight %, preferably less than 8 weight %, and more preferably less than 5 weight %, and more preferably less than 2 weight % of the total weight of the active layer. The polymer binder is present in an amount greater than 0.1 weight % of the total weight of the active layer. The lower weight of the polymer binder in the active layer promotes a lower reduction in the electrical conductivity of the active layer. In other words, the lower the amount of the polymer binder, the greater the electrical conductivity of the active layer. The active layer is arranged on a current collector and comprises a related (anode or cathode) active material, a conductive additive and a polymer binder.

[0113] The electrode forming slurry contains an active material. The active material may be different depending on whether the slurry is used to form an anode active layer or a cathode active layer.

[0114] Anode active materials include some of the aforementioned carbonaceous materials, hard carbon, silicon, silicon mixed with graphite, carbon-coated silicon particles, Li4Ti5O 12 ; transition metals such as tin, metal oxides, metal sulfides (e.g., TiO2, FeS, etc.), lithium metal and alloys, or combinations thereof. Exemplary active materials may include graphite, hard carbon, activated carbon, nanoform carbon, silicon, silicon oxide, carbon-coated silicon nanoparticles, or combinations thereof. In some such embodiments, the anode active material may be intercalated with lithium (e.g., using pre-lithiation methods known in the art).

[0115] Hard carbon is a solid form of carbon that cannot be converted into graphite by heat treatment, even at temperatures up to 3000°C. It is also called coke or non-graphitizable carbon. Hard carbon is made by heating a carbonaceous precursor to about 1000°C in the absence of oxygen. Precursors of hard carbon are especially polyvinylidene chloride (PVDC), lignin and sucrose. Other precursors, such as polyvinyl chloride (PVC) and petroleum coke, produce soft carbon or graphitized carbon. Soft carbon can be easily converted into graphite by heating to 3000°C.

[0116] The cathode active material may include lithium cobalt oxide (LCO, sometimes called "lithium cobaltate" or "spodumene" - one of its variants is LiCoO2); lithium nickel manganese cobalt oxide (NMC, with a variant formula of LiNiMnCo); lithium manganese oxide (LMO, with a variant formula of LiMn2O4, Li2MnO3, etc.); lithium nickel cobalt aluminum oxide (LiNiCoAlO2 and its variants such as NCA) and lithium titanate oxide (LTO, one variant formula of Li4Ti5O 12 ); lithium iron phosphate oxide (LFP, a variant is LiFePO4), lithium nickel cobalt aluminum oxide (and its variants such as NCA) and other similar materials, spinel (LiMn2O4, LiNi 0.5 Mn1.5 O4), polyanion cathodes (LiV2(PO4)3), and other lithium transition metal oxides. Surface coated and / or doped cathode materials mentioned above, such as LiNbO3-coated LiMn2O4 and Al-doped LiMn2O4, may also be used. Low voltage cathode materials such as lithiated metal oxides / sulfides (e.g., LiTiS2), lithium sulfide, and sulfur may also be used.

[0117] Other variations of the foregoing may be included. In some embodiments where NMC is used as the active material, a nickel-rich NMC may be used. For example, in some embodiments, a variation of the NMC may be LiNi x Mn y Co (1-x-y) O2、LiNi x Mn v Al (1-x-y) O2、LiNi x Mn (1-x) O2、Li 1+x MO2, wherein x is equal to or greater than about 0.7, 0.75, 0.80, 0.85 or greater, and wherein y is less than 0.15, preferably less than 0.1. In some embodiments, NMC811 may be used, wherein in the preceding formula, x is about 0.8 and y is about 0.1.

[0118] The anode active material may be used in an amount of 60 to 99 wt % based on the total weight of the anode active layer, respectively. The cathode active material may be used in an amount of 70 to 90 wt % based on the total weight of the cathode active layer, respectively.

[0119] In one embodiment, the electrode forming slurry may also optionally contain a small portion of a solid electrolyte. The solid electrolyte generally comprises a pseudo binary sulfide, a pseudo ternary sulfide, a pseudo quaternary sulfide, or a combination thereof. Examples of pseudo binary sulfides include the Li2S-P2S5 system (e.g., Li3PS4, Li7P3S 11 and Li 9.6 P3S 12 ), Li2S-SnS2 system (e.g., Li4SnS4), Li2S-SiS2 system, Li2S-GeS2 system, Li2S-B2S3 system, Li2S-Ga2S3 system, Li2S-P2S3 system, Li2S-Al2S3 system, or a combination thereof. Examples of pseudo-ternary sulfides include Li2O-Li2S-P2S5 system, Li2S-P2S5-P2O5 system, Li2S-P2S5-GeS2 system (e.g., Li 3.25 Ge 0.25 P 0.75 S4 and Li 10GeP2S 12 ), Li2S-P2S5-LiX system (wherein X=F, Cl, Br or I, examples of which include Li6PS5Br, Li6PS5Cl, L7P2S8I and Li4PS4I), Li2S-As2S5-SnS2 system (e.g. Li 3.833 Sn 0.833 As 0.166 S4), Li2S-P2S5-Al2S3 system, Li2S-LiX-SiS2 (where X = F, Cl, Br or I, examples of which include 0.4LiI·0.6Li4SnS4 and Li 11 Si2PS 12 ).

[0120] The active layer may contain the pseudo binary sulfide, pseudo ternary sulfide, pseudo quaternary sulfide, or a combination thereof in an amount of 10 to 40 wt % based on the total weight of the active layer.

[0121] The electrode forming slurry can be manufactured in several different ways. The active layer manufactured using the electrode forming slurry can be formed in a one-step process or in multiple steps. In one embodiment, in a method of manufacturing the electrode forming slurry, the synergistic solvent composition, the conductive composition, the polymer binder, the anode or cathode active material and the optional solid electrolyte can be mixed for an appropriate amount of time in a single mixing device such as a mixer to form a slurry. The mixing time can be 30 minutes to 5 hours. The slurry containing the appropriate active material is then arranged on the corresponding current collector to form an anode or cathode. The slurry after being arranged on the collector is dried to form an active layer.

[0122] Drying may be performed at a temperature of 50 to 80° C. for a period of 30 minutes to 10 hours, preferably 1 to 5 hours.

[0123] The electrode forming slurry can also be manufactured in a two-step process. In the first step, the required active material (anode active material or cathode active material) is blended with a conductive additive and a low polarity solvent (first solvent), and mixed for a period of 30 minutes to 5 hours to form a first slurry. If necessary, an optional small amount of solid electrolyte can also be added to the blend. Mixing is carried out in a planetary mixer, although other mixers such as Waring blender, Henschel mixer, single screw and multi-screw extruders can also be used.

[0124] In the second step, the polymer binder is mixed with an ether-based solvent (second solvent) and mixed for 30 minutes to 5 hours to form a second slurry. If necessary, an optional small amount of solid electrolyte can also be added to the second slurry. As mentioned above, the ether-based solvent is compatible with the polymer binder and can solubilize a portion of the binder or can completely solubilize the entire volume of the binder. Although the term "second slurry" is used here, it should be noted that the product of the second step can be a solution.

[0125] The first slurry is then mixed with the second slurry to form an electrode forming slurry. The mixing of the first and second slurries can be carried out in an extruder or a planetary mixer. It can therefore be an intermittent process or a continuous process. The resulting electrode forming slurry is then applied to a suitable current collector (applied to the anode current collector to form an anode, or applied to the cathode current collector to form a cathode) and dried. Compression can be optionally applied during the drying process to produce a compact electrode.

[0126] The drying may be performed at a temperature of 50 to 80° C. for 30 minutes to 10 hours, preferably 1 to 5 hours. During the drying process, the low-polarity solvent and the ether-based solvent evaporate to produce a dry electrode (anode or cathode, as the case may be).

[0127] In one embodiment, the synergistic co-solvent composition can also be used to make a solid electrolyte. The low polarity solvent (first solvent, such as anisole) can first be mixed with a solid electrolyte (these are listed above, an example of which is Li6PS5Cl) in a desired amount to form a first blend. The ether-based solvent (second solvent, such as dimethyl ether) is then mixed with a binder in a desired amount to form a second blend. The corresponding blending is preferably carried out in a planetary mixer. Other mixers, such as those listed above, can also be used. The first blend and the second blend are then mixed together in a planetary mixer to make an electrolyte slurry containing a co-solvent. The electrolyte slurry is then applied to a non-sticky substrate and dried at 60°C (during this process the co-solvent is dried and removed from the slurry). After drying, the solid electrolyte can be compression molded, or can be crushed to form a powder. The solid electrolyte can then be added to a battery pack in the form of a plate or in the form of a powder. The solid electrolyte typically surrounds the anode and cathode in the battery pack, such as Figure 1 As seen in .

[0128]

[00136] The compositions and methods detailed above can be described in detail in the following non-limiting examples. Example

[0129] Example 1

[0130] This example was conducted to demonstrate the fabrication of a cathode for a solid state electrolytic cell. Figure 2 The mixing steps are depicted. In the first mixing step (300), the cathode active material (NMC, 1.4 grams (g)), the conductive additive (Super P, 0.01 grams) and the solid electrolyte (Li6PS5Cl, 0.59 grams) are mixed with a low polarity solvent (302) (anisole, 0.7 grams) in a planetary mixer (400) at 1000 rpm for 2 hours to form a first slurry (referred to as the electrode suspension (502)). In the second step, the binder (306) (PVDF-HFP, 0.04 grams) and the ether-based solvent (308) (dimethyl ether, 2.1 grams) are mixed in a planetary mixer (402) at 60° C. for 1 hour to form a second slurry (504) (also referred to as a binder solution). The first slurry and the second slurry were then mixed together in a planetary mixer (404) at 600 rpm for 30 minutes to form an electrode forming slurry (506) (also referred to as cathode slurry), which was disposed on a current collector and dried at 60°C for 30 minutes to form a cathode (508).

[0131] Example 2

[0132] This example was conducted to demonstrate the structural and performance improvements of a battery using the synergistic co-solvent composition disclosed herein compared to a battery not using the synergistic co-solvent composition. Two identical batteries were prepared having the same anode active layer and cathode active layer, except that in one case, the cathode active layer used the disclosed co-solvent composition during manufacture, while the comparative battery used only an ether-based solvent (DME) as the solvent for processing the cathode active layer. Both batteries (the experimental battery using the co-solvent and the comparative battery using only DME) were subjected to a series of tests, the results of which are shown in Table 1. Figure 3A , 3B and 3C. The test geometry for the battery pack was a pellet cell. The anode active layer was a lithium-indium alloy with a thickness of 100 μm. Figure 3A and 3C 0.2 Coulomb (C) Figure 3B The sheet battery was charged to a cut-off voltage of 3.68V at 0.2C, 0.5C, 1C, 2C, 3C and 5C (in the figure), followed by a constant voltage charge of 3.68V until the current rate was lower than 0.5C, and then a constant current discharge to 2.0V. The test temperature was room temperature (25°C). The voltage range was 2.0V to 3.68V.

[0133] Figure 3A , 3B3C and 3C are graphs detailing the charge-discharge characteristics, rate capability, and cycling at room temperature of two battery packs: an experimental battery pack (802) whose electrodes were made using a co-solvent and a comparative battery pack (800) whose electrodes were made using a single solvent, DME. Figure 3A is a graph of voltage (V) (602) versus capacity (mAh / g) (604) for the first charge and discharge cycle measured on an experimental battery (802) and a comparative battery (800) at a constant current rate of 0.2C. Figure 3B is a graph of measured capacity (mAh / g) (606) versus cycle number (608) for the experimental battery (802) and the comparative battery (800). These measurements were performed at variable current rates of 0.2C, 0.5C, 1C, 2C, 3C, and 5C.

[0134] Figure 3C It is a graph of the measured capacity (mAh) (612) versus the number of cycles (614) for the experimental battery pack (802) and the comparative battery pack (800) when cycled at a current rate of 0.5C at room temperature.

[0135] From these three figures, it can be seen that the electrodes fabricated using the co-solvent can provide higher first-cycle Coulombic efficiency, enhanced 1C discharge capacity, and better battery cycling performance compared to the electrodes fabricated using only a single solvent (DME).

[0136] In one embodiment, the final electrode forming slurry can be subjected to rolling to remove the solvent and further shear the mixed components. The rolled sheet obtained by the rolling operation can then be inserted into the current collector and bonded to the current collector using a polymer binder as a binder or by using an additional conductive binder.

[0137] The terms "a" and "an" do not indicate a limitation of quantity, but rather indicate the presence of at least one of the referenced item. The term "or" means "and / or" unless the context clearly indicates otherwise. Reference to "aspects" throughout the specification means that a particular element (e.g., feature, structure, step, or characteristic) described in conjunction with that aspect is included in at least one aspect described herein, and may or may not be present in other aspects. Furthermore, it is to be understood that the described elements may be combined in any suitable manner in the various aspects.

[0138] When an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present.

[0139] Unless specified to the contrary herein, all test standards are the most recent standards in effect as of the filing date of the present application, or, if priority is claimed, the filing date of the earliest priority application in which the test standards appeared.

[0140] Unless defined otherwise, technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs.

[0141] Although the above disclosure has been described with reference to exemplary embodiments, it will be appreciated by those skilled in the art that various changes may be made and elements thereof may be replaced with equivalents without departing from the scope thereof. In addition, many modifications may be made to adapt specific circumstances or materials to the teachings of the disclosure without departing from the substantive scope of the disclosure. Therefore, it is intended that the disclosure is not limited to the specific embodiments disclosed, but will include all embodiments falling within its scope.

Claims

1. A method for producing an electrode forming slurry, comprising: Mixing an active material, a conductive material, and an optional solid electrolyte together with a low polarity solvent; wherein the low polarity solvent has a dipole moment of less than 4 and a boiling point greater than 100° C. to form a first slurry; wherein the active material is an anode active material or a cathode active material; mixing a polymer binder and an ether-based solvent together to form a second slurry; and The first slurry is mixed with the second slurry to form an electrode-forming slurry.

2. The method of claim 1, further comprising disposing the electrode-forming slurry on a current collector and subjecting the current collector to an elevated temperature to form the electrode.

3. The method of claim 1, wherein the low polarity solvent has a structure represented by the following formula: C n H 2n+2 (1); or C n H 2n (2); wherein C is carbon, H is hydrogen, and n is an integer greater than 5, and wherein the structure of formula (1) or formula (2) is substituted or unsubstituted.

4. The method of claim 1, wherein the low polarity solvent is pentane, cyclopentane, hexane, cyclohexane, heptane and isomers thereof, toluene, ethylbenzene, p-xylene, m-xylene, o-xylene, anisole or a combination thereof.

5. The method of claim 1, wherein the ether-based solvent comprises an ether having a structure defined by formula (3): C 2n H 2n+2 O (3), wherein C is carbon, H is hydrogen, O is oxygen, and wherein n is an integer greater than 1; and wherein the structure of formula (3) is substituted or unsubstituted.

6. The method of claim 1, wherein the ether-based solvent is dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, dimethoxymethane, tetraethylene glycol, methyl tert-butyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, tetrahydrofuran (THF), dioxane, diisopropyl ether, 2-butoxyethanol, cyclopentyl methyl ether, 2-methyltetrahydrofuran, or a combination thereof.

7. The method of claim 1, wherein the solid-state electrolyte is a pseudo-binary sulfide, a pseudo-ternary sulfide, a pseudo-quaternary sulfide, or a combination thereof.

8. The method of claim 1, wherein the solid electrolyte is Li6PS5Cl.

9. A method of manufacturing a solid electrolyte for a solid-state battery, comprising: A low polarity solvent and an ether-based solvent are mixed with a solid electrolyte and a polymer binder; wherein the low polarity solvent has a dipole moment less than 4 and a boiling point greater than 100° C.; wherein the solid electrolyte is a pseudo-binary sulfide, a pseudo-ternary sulfide, a pseudo-quaternary sulfide, or a combination thereof.

10. A battery pack comprising: Anode current collector; An anode active layer disposed on the anode current collector; wherein the anode active layer comprises an anode active material; a polymer binder and a conductive additive; cathode current collector; A cathode active layer disposed on a cathode current collector; wherein the cathode active layer comprises a cathode active material; a polymer binder, a solid electrolyte, and a conductive additive; and A solid electrolyte; wherein the solid electrolyte contacts an anode active layer and a cathode active layer; and wherein the solid electrolyte comprises a blend of a polymer binder and a pseudo binary sulfide, a pseudo ternary sulfide, a pseudo quaternary sulfide, or a combination thereof.